2012
DOI: 10.1111/j.1600-6143.2012.04087.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Replication Kinetics in Solid Organ Transplant Recipients Managed by Preemptive Therapy

Abstract: After allotransplantation, cytomegalovirus (CMV) may be transmitted from the donor organ, giving rise to primary infection in a CMV negative recipient or reinfection in one who is CMV positive. In addition, latent CMV may reactivate in a CMV positive recipient. In this study, serial blood samples from 689 kidney or liver transplant recipients were tested for CMV DNA by quantitative PCR. CMV was managed using preemptive antiviral therapy and no patient received antiviral prophylaxis. Dynamic and quantitative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
209
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(236 citation statements)
references
References 25 publications
11
209
4
1
Order By: Relevance
“…CMV disease incidence was 16.9% in high-risk patients (CMV Dþ/RÀ) and 4.4% in the intermediate-risk patients (CMV Rþ). These numbers are similar to or lower than those observed in the most recent published prospective cohort studies (9,26) or randomized controlled trials (15,16,27), reflecting the improved management on the prevention of CMV disease over the last years. Some patients took sequentially more than one drug, so the addition of numbers may result in >100%.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…CMV disease incidence was 16.9% in high-risk patients (CMV Dþ/RÀ) and 4.4% in the intermediate-risk patients (CMV Rþ). These numbers are similar to or lower than those observed in the most recent published prospective cohort studies (9,26) or randomized controlled trials (15,16,27), reflecting the improved management on the prevention of CMV disease over the last years. Some patients took sequentially more than one drug, so the addition of numbers may result in >100%.…”
Section: Discussionmentioning
confidence: 43%
“…However, Dþ/RÀ patients were not included (14) or represented only a minority of all patients included in these trials (10,11). Some studies showed a marked benefit of the preemptive approach in Dþ/RÀ patients (28,29), although recent studies have shown a similar or even higher incidence of CMV diseases compared to the use of antiviral prophylaxis (9,30). In a French study, 80 Dþ/RÀ kidney transplant recipients followed preemptively were compared to a historical cohort of 32 Dþ/RÀ patients who received antiviral prophylaxis (30).…”
Section: Impact Of CMV Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation represents a real-world scenario, dealing specifically with patients experiencing clinically manifest CMV disease, thereby extending data from previous clinical trials addressing asymptomatic CMV infection/replication. 5,7 Although "strain-specific" mismatch is cited as an underlying mechanism for this phenomenon, 9 substantial data exist that question this hypothesis (discussed further below). We therefore investigated whether donor-recipient HLA mismatch impaired development of cognate cellular immunity to CMV within transplanted donor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, historical evidence suggests that D+R+ transplantation is associated with increased disease rates compared with D2R+ transplantation. 4 Also, two recent trials 5,6 and a single-center study 7 showed higher infection rates in D+R+ than in D2R+ transplantation. Because these latter studies focused on (often asymptomatic) CMV infection, rather than symptomatic disease, and because all used antiviral prophylaxis or pre-emptive therapy for CMV infection, it remains unclear whether disease rates differ between D+R+ and D2R+ transplantation, particularly under contemporary immunosuppression without antiviral prophylaxis.…”
mentioning
confidence: 99%